(untitled) (Revista de Ciências Agroveterinárias, 2004)
The aim of this work was to stablish relations between California Mastitis Test (CMT), Somatic Cell Counting (SCC) and the bacterial isolation. Absence of clinical mastitis was verified by inspection and palpation in 244 goats of different races and in different periods of lactation. 24% of the mammary halves presented bacterial growth. Staphylococcus aureus (28%) and negative coagulate Staphylococcus (29%) were identified. Using bacteriology as standard, it was determined that CMT presents 59.2% of sensitivity, 78.2% of specificity, 56.9% of Positive Predictive Value (PPV), 79.8% of Negative Predictive Value (NVP) and medium kappa coefficient (k = 0,37) and the CCS presents 18% of sensitivity, 94% of specificity, 45.5% of PPV, 75.3% of NVP and medium kappa coefficient (k = 0,16), while methods of diagnosis of the mastitis in goat. The low sensitivity coefficients showed by CMT and CCS indicate that both tests should not be used as selection methods to identify mastits.